2022
DOI: 10.3390/ijms23031811
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oncostatin M and Its Receptor Complexes in Cardiomyocyte Protection, Regeneration, and Failure

Abstract: Oncostatin M (OSM), a member of the interleukin-6 family, functions as a major mediator of cardiomyocyte remodeling under pathological conditions. Its involvement in a variety of human cardiac diseases such as aortic stenosis, myocardial infarction, myocarditis, cardiac sarcoidosis, and various cardiomyopathies make the OSM receptor (OSMR) signaling cascades a promising therapeutic target. However, the development of pharmacological treatment strategies is highly challenging for many reasons. In mouse models o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 143 publications
2
14
0
Order By: Relevance
“…Oncostatin-M-specific receptor subunit beta (OSMR), a member of the interleukin 6 (IL6) receptor family, functions as a major mediator of cardiomyocyte remodeling under pathological Frontiers in Genetics frontiersin.org conditions (Kubin et al, 2022). The involvement of OSMR in multiple human heart diseases such as aortic stenosis, myocardial infarction, myocarditis, and various cardiomyopathy makes OSMR a promising new therapeutic target (Kubin et al, 2022). Wu et al (2021) found that long noncoding RNA Pvt1 regulates pathological cardiac hypertrophy through miR-196b-mediated OSMR regulation.…”
Section: Gene Namesmentioning
confidence: 99%
“…Oncostatin-M-specific receptor subunit beta (OSMR), a member of the interleukin 6 (IL6) receptor family, functions as a major mediator of cardiomyocyte remodeling under pathological Frontiers in Genetics frontiersin.org conditions (Kubin et al, 2022). The involvement of OSMR in multiple human heart diseases such as aortic stenosis, myocardial infarction, myocarditis, and various cardiomyopathy makes OSMR a promising new therapeutic target (Kubin et al, 2022). Wu et al (2021) found that long noncoding RNA Pvt1 regulates pathological cardiac hypertrophy through miR-196b-mediated OSMR regulation.…”
Section: Gene Namesmentioning
confidence: 99%
“…The Type I receptor complex is formed by the OSM receptor (IL-31RB) and the leukemia inhibitory factor receptor (LIF-R), also known as glycoprotein 130 (gp130), whereas the Type II receptor complex consists of IL-31RB and IL-31RA [ 22 , 23 , 24 ]. The role of OSM and its receptor complexes in the context of cardioprotection, regeneration, and failure has been recently reviewed in detail [ 25 ]. The signaling pathways and functional effects triggered by the interactions between OSM and its receptors are not yet fully understood and vary between cell types and physiological states, but these interactions induce the activation of Janus Kinase (JAK) family members (JAK1-2 and TYK2) through tyrosine phosphorylation, which in turn induces the activation and nuclear translocation of STAT proteins (STAT1, 3, 5A, and B) in receptor cells.…”
Section: Introductionmentioning
confidence: 99%
“…OSM has also been reported to promote cardiomyocyte dedifferentiation and cardiac tissue recovery after cardiac injury [ 30 , 31 ]. Strikingly, although OSM is considered to be a proinflammatory cytokine that promotes fibrosis in different tissues, including liver and lung tissue [ 32 , 33 ], during ischemic cardiac remodeling, OSM secreted by Ly6Chi monocytes/macrophages suppresses cardiac fibroblast activation by inhibiting transforming growth factor beta 1 (TGF-β1) [ 19 ] and ECM deposition [ 25 , 34 ]. Moreover, in a model of myocardial infarction, intraperitoneal injection of recombinant OSM (rOSM) improved cardiac function at least in part by promoting the shift of cardiac Mφ from M1 to M2 phenotype [ 35 ] and treatment of mice subjected to myocardial infarction with rOSM-alleviated post-infarction cardiac remodeling through the enhancement of cardiomyocyte autophagy [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, Oncostatin M (OSM) is one of the newly discovered bone reconstruction regulatory proteins (18). It is mainly secreted by macrophages, T cells, and dendritic cells and has a variety of biological activities, such as promoting bone formation, stimulating hematopoiesis, and promoting cell proliferation (19,20). OSMR/gp130 and LIFR/gp130 are the two main receptors of OSM; OSMR, as one of the specific receptors, is mainly distributed on the surface of bone marrow stem cells and osteoblasts (21).…”
Section: Introductionmentioning
confidence: 99%